Abdominal Wall Endometriosis : Case Series - Hendrik B. Mengga; Toby H. Wiranegara (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
Abdominal wall endometriosis (AWE) is an uncommon presentation of extra-pelvic endometriosis, most frequently developing following gynaecological surgeries, particularly caesarean sections. The study aims to describe the clinical characteristics, diagnostic process, surgical management, and outcomes in two post-caesarean patients diagnosed with AWE, while highlighting the importance of early recognition. This research is a retrospective descriptive case series. We used purposive sampling of two patients with histopathologically confirmed AWE. Two women, aged 41 and 44 years, presented with a gradually enlarging palpable mass in the right lower abdominal wall, accompanied by local tenderness and cyclical pain during menstruation. Symptom duration was 14 years in the 41-year-old and 7 years in the 44-year-old, both with a history of caesarean section. Contrast-enhanced CT scans revealed soft tissue lesions within the rectus abdominis muscle extending into subcutaneous tissue. Both patients underwent wide surgical excision with adequate margins, followed by polypropylene mesh reconstruction due to lesion size. Histopathology confirmed ectopic endometrial glands and stroma. Both patients recovered without complications and reported complete resolution of symptoms at follow-up. Masses in the right lower abdominal wall with a history of caesarean section are frequently misdiagnosed due to multiple differential diagnoses, including desmoid tumours, hernias, lipomas, hematomas, and suture granulomas. AWE should be considered in women presenting with cyclical abdominal wall pain and a history of caesarean section. Early wide surgical excision with appropriate reconstruction provides excellent outcomes. Improved clinical awareness is essential to reduce diagnostic delays and enhance patient quality of life.